GREBENSK COSSACKS IN THE SERVICE OF THE ROMANOV DYNASTY (1700-1762) - Cekulaev, N D (History, Archeology and Ethnography of the Caucasus, 2016)
Basing on the available sources and achievements of historiography, the author of the article examines the complexity and inconsistency of service of Grebensk Cossacks, one of the numerous Cossack troops of the Russian state.